Measurement of transverse polarization of Λ and hyperons inside jets in unpolarized proton-proton collisions at GeV - STAR Collaboration (Journal of High Energy Physics, 2026)
A surprisingly large transverse polarization of Λ hyperons in unpolarized hadron-nucleon/nucleus collisions has been observed for 50 years, and the origin of this polarization remains an important open question. Recently, theoretical frameworks have advanced in describing this puzzle with the polarizing fragmentation function (PFF). We report the first measurement of Λ and transverse polarization inside jets in unpolarized proton-proton collisions, which is directly attributed to the PFF. The polarization is measured as a function of the jet transverse momentum, the fraction of the jet momentum carried by hyperons, and the transverse momentum of hyperons relative to the jet axis. Covering a wide jet-energy range, these data provide the first constraints on the gluon PFF and allow tests of TMD evolution and its universality. © The Author(s) 2026.
Keywords: Hadron-Hadron Scattering; Jets; Polarization; Proton-Proton Scattering; dept.phy